2011
DOI: 10.1093/icesjms/fsr178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an anticyclonic eddy on the summer nutrient and chlorophyll a distributions in the Ulleung Basin, East Sea (Japan Sea)

Abstract: Kim, D., Yang, E. J., Kim, K. H., Shin, C-W., Park, J., Yoo, S., and Hyun, J-H. 2012. Impact of an anticyclonic eddy on the summer nutrient and chlorophyll a distributions in the Ulleung Basin, East Sea (Japan Sea). – ICES Journal of Marine Science, 69: 23–29. The impact of the anticyclonic Ulleung Warm Eddy (UWE) on the vertical distributions of nutrient and chlorophyll a (Chl a) concentrations in the Ulleung Basin (UB) was investigated during the contrasting summers of 2005 and 2007. The physical structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 34 publications
3
56
0
4
Order By: Relevance
“…A similar high C org content as in the UB is rarely found in deep-sea sediment underlying oxic bottom water at depths exceeding 2000 m, except for a Chilean upwelling site (Lee et al, 2008). This high C org content in the UB is mainly associated with the combination of enhanced biological production resulting from the formation of coastal upwelling (Hyun et al, 2009a), enhanced new production in summer (Kwak et al, 2013), occurrence of an intrathermocline eddy resulting in the extraordinary subsurface chlorophyll a maximum (Kim et al, 2012), high C org accumulation rates exceeding 2 g C m −2 year −1 (Lee et al, 2008), and high export production . Consequently, high benthic mineralization resulting from the high C org in the sediment implied that the UB is a biogeochemical hotspot where significant turnover of organic matter and nutrient regeneration occur.…”
Section: The Ub As a Biogeochemical Hotspotmentioning
confidence: 57%
“…A similar high C org content as in the UB is rarely found in deep-sea sediment underlying oxic bottom water at depths exceeding 2000 m, except for a Chilean upwelling site (Lee et al, 2008). This high C org content in the UB is mainly associated with the combination of enhanced biological production resulting from the formation of coastal upwelling (Hyun et al, 2009a), enhanced new production in summer (Kwak et al, 2013), occurrence of an intrathermocline eddy resulting in the extraordinary subsurface chlorophyll a maximum (Kim et al, 2012), high C org accumulation rates exceeding 2 g C m −2 year −1 (Lee et al, 2008), and high export production . Consequently, high benthic mineralization resulting from the high C org in the sediment implied that the UB is a biogeochemical hotspot where significant turnover of organic matter and nutrient regeneration occur.…”
Section: The Ub As a Biogeochemical Hotspotmentioning
confidence: 57%
“…A few hypotheses have been suggested as the main cause of the high primary productivity in the UB. These include physical processes such as coastal upwelling and mesoscale eddies [Hyun et al, 2009;Yoo and Park, 2009;Kim et al, 2012;Lim et al, 2012]. A recent study that compared summer primary productivity in the UB with that in the subtropical western Pacific and the East China Sea suggested that the relatively high rates of primary productivity in the UB is supported by increased nitrate (NO 3 ) supply from nutrient-rich deeper waters to the euphotic zone because of the shallow pycnocline in summer [Kwak et al, 2013a].…”
Section: Introductionmentioning
confidence: 99%
“…7). It is probable that these increases are the maximum surface expression developed below the surface, as reported for ITEs in other oceanic regions (McGillicuddy et al, 2007;Kim et al, 2011). In the JFA, high surface Chl-a concentrations have been detected reaching values of ~2 mg m -3 in AS island and ~1 mg m -3 in the RC-SC islands (Pizarro et al, 2006).…”
Section: Discussionmentioning
confidence: 76%